Terrestrial carbon inputs to inland waters: A current synthesis of estimates and uncertainty - Drake, Travis W.; Raymond, Peter A.; Spencer, Robert G. M. (Limnology and oceanography letters, 2018)
Globally, inland waters receive a significant but ill‐defined quantity of terrestrial carbon (C). When summed, the contemporary estimates for the three possible fates of C in inland waters (storage, outgassing, and export) highlight that terrestrial landscapes may deliver upward of 5.1 Pg of C annually. This review of flux estimates over the last decade has revealed an average increase of ∼ 0.3 Pg C yr−1, indicating a historical underestimation of the amount of terrestrial‐C exported to inland waters. The continual increase in the estimates also underscores large data gaps and uncertainty. As research continues to refine these aquatic fluxes, especially C outgassed from the humid tropics and other understudied regions, we expect the global estimate of terrestrial‐C transferred to inland waters to rise. An important implication of this upward refinement is that terrestrial net ecosystem production may be overestimated with ramifications for modeling of the global C cycle.